Surfactant phospholipids act as molecular switches for premature induction of quorum sensing-dependent virulence in Pseudomonas aeruginosa. Issue 1 (1st January 2020) - Kuang, Zhizhou; Bennett, Richard C.; Lin, Jingjun; Hao, Yonghua; Zhu, Luchang; Akinbi, Henry T.; Lau, Gee W.
ABSTRACT: The virulence behaviors of many Gram-negative bacterial pathogens are governed by quorum-sensing (QS), a hierarchical system of gene regulation that relies on population density by producing and detecting extracellular signaling molecules. Although extensively studied under in vitro conditions, adaptation of QS system to physiologically relevant host environment is not fully understood. In this study, we investigated the influence of lung environment on the regulation of Pseudomonas aeruginosa virulence factors by QS in a mouse model of acute pneumonia. When cultured under laboratory conditions in lysogeny broth, wild-type P. aeruginosa strain PAO1 began to express QS-regulated virulence factors elastase B (LasB) and rhamnolipids (RhlA) during transition from late-exponential into stationary growth phase. In contrast, during acute pneumonia as well as when cultured in mouse bronchial alveolar lavage fluids (BALF), exponential phase PAO1 bacteria at low population density prematurely expressed QS regulatory genes lasI-lasR and rhlI-rhlR and their downstream virulence genes lasB and rhlA . Further analysis indicated that surfactant phospholipids were the primary components within BALF that induced the synthesis of N -(3-oxododecanoyl)-L-homoserine lactone (C12-HSL), which triggered premature expression of LasB and RhlA. Both phenol extraction and phospholipase A2 digestion abolished the ability of mouse BALF to promote LasB and RhlA expression. In contrast, provision of the major surfactant phospholipid dipalmitoylphosphatidylcholine (DPPC) restored the expression of both virulence factors. Collectively, our study demonstrates P. aeruginosa modulates its QS to coordinate the expression of virulence factors during acute pneumonia by recognizing pulmonary surfactant phospholipids.